Do Maternal Vitamin D Levels Influence Vitamin D Levels in Preterm Neonates? - M. Panda; J. McIntosh; T. Chaudhari; A. L. Kent (Hindawi Limited, 2019)
Objective. To determine the prevalence of Vitamin D (VitD) deficiency/insufficiency in mothers of preterm neonates less than or equal to 32 weeks of gestation and determine if the current level of VitD supplementation used for preterm neonates is appropriate. Design. Prospective study from 10th May 2015 to 1st November 2016. Setting. Neonatal Intensive Care Unit at the Canberra Hospital. Patients. Mothers and their preterm neonates born less than or equal to 32 weeks gestation. Interventions. Maternal VitD levels were obtained within 3-4 days following delivery. Neonatal VitD levels were obtained in the first 3-4 days of life, at 3-4 weeks of age, and at 6-8 weeks of age. Demographic data and data on VitD intake from parenteral nutrition, enteral feeds, and vitamin supplementation agents were collected. Results. 70 neonates were enrolled into the study. Median gestation was 29 (27-30) weeks and median birth weight 1197 (971.2-1512.5) grams. Median maternal VitD level was 54.5 (36-70.7) nmol/L, median neonatal Vit D level at birth was 57 (42-70) nmol/L. Median Vit D level at 3 weeks and 6 weeks were 63.5 nmol/L (53-80.2) nmol/L and 103 (71.5-144) nmol/L respectively. 22/55 (40%) mothers were VitD deficient/insufficient. 25/70 (36%) neonates were VitD deficient/insufficient at birth. Of those neonates who were VitD deficient/insufficient at birth 5/25(10%) were deficient/insufficient at 6 weeks. The median intake of VitD at 6 weeks was 826.5 (577.5-939.5) IU/day. Conclusions. VitD deficiency/insufficiency in mothers of preterm neonates and in preterm neonates at birth is common. Routine screening of maternal VitD and their preterm neonates along with individualized supplementation regimens in mothers and preterm infants may optimize VitD status and reduce risk of ongoing VitD deficiency/insufficiency.